The theory of επινοια in st. Basil of Caesarea and Eunomius of Cyzicus: philosophical and theological background - Panagopoulos, Georgios D. (Vox Patrum, 2018)
In the paper our attention is focused on the way in which both Saint Basil of Caesarea and his opponent, the anomoian Eunomius of Cyzicus, integrate in their theological thought the philosophical teaching about the formation of concepts (™p…noia) in human mind and their relation to the external objects. Our inquiry will provide the evidence that the two theologians are acquainted with the same philosophical material concerning human mind’s concepts; nevertheless each of them opted to use a different element from the related philosophical traditions in order to provide support to different theological purposes. Eunomius’ rationalistic doctrine of God’s knowledge, which goes hand in hand with his account of human language and mind, prompted Saint Basil to advance an empirical epistemological view that both makes possible a talk about God based on sense data and keeps fully intact the transcendence of God’s essence.